MINISTERIAL LEADERSHIP DEVELOPMENT AND PROFESSIONAL ENHANCEMENT IN URBAN INDONESIAN CHURCHES - Rindu, Kiem; Onibala, Ronald Stevly (Scriptura Indonesia, 2023)
This qualitative research examines ministerial leadership development effectiveness in Bekasi City through comprehensive analysis of perspectives from pastors, theological educators, and church workers. The study employs semi-structured interviews with ten key stakeholders to assess current professional development approaches, identify competency gaps between leadership preparation and ministry demands, and develop evidence-based enhancement frameworks. Findings reveal strong foundational capacity alongside critical gaps in systematic programming, particularly in social justice advocacy, cultural competency, and community engagement training. The research demonstrates substantial correlation between systematic professional development and enhanced leadership effectiveness, organizational capacity, and community impact outcomes. Collaborative partnership development emerges as the highest-impact improvement opportunity, while mentorship programs and technology integration represent critical enhancement priorities. Results indicate exceptional readiness for coordinated development initiatives that leverage existing institutional capacity rather than requiring fundamental transformation. The study contributes valuable insights regarding Christian leadership development in Southeast Asian urban contexts while providing transferable frameworks for ministerial professional enhancement in diverse cultural environments. Recommendations emphasize systematic programming establishment, inter-institutional collaboration, and sustainable capacity building that addresses both individual competency and collective organizational effectiveness for enhanced urban ministry impact.